تأثير تراكيز مختلفة من الملوحة في إنبات بذور بعض أصول الحمضيات ونمو بادراتها (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2018)
The study aimed to determine the effect of sodium chloride (NaCl) solution on the germination of the seeds of some citrus rootstocks. In this study, the seeds of rootstocks used: Citromelo, Carizo citrang, Troyer citrang, Trifoliate orange, Cleopatra mandarin, and Sour Orange. The experiment was designed in a Randomized Complete Block Design, and included four treatments, each with 5 replicates and each 20-seed repeater. The results analyzed by using SPSS and ANOVA to determine the Significant Differences between treatments and rootstocks studied. After analyzing the observed data for treatments and rootstocks, the study showed that there is no reciprocal effects between the studied rootstocks and the saline treatments, increased saline concentration according to the treatments reduces the percentage of germination at the level of the single rootstock. However, at the level of all rootstocks, there are no significant differences at the effect of the treatments in rootstocks seed germination, where the rootstocks are similar in the rate of decrease in germination depending on the salinity treatments, there is a convergence in the percentages of seed germination in the first treatment (control) and the second treatment (1000 ppm). Then we note that the percentage of germination in the third and fourth treatments (2000, 3000 ppm) is reduced, With the exception of Citromelo rootstock seeds whose percentage of germination was not affected by an increase in saline concentrations, as well as the Troyer citrang rootstock, whose seed germination was only slightly affected in the fourth treatment. As for the effect of sodium chloride solution on the continuation of seedling growth, it is noted that the highest percentage of seedling death was Cleopatra mandarin rootstock, It reached 69.31% in the fourth treatment (3000ppm), whereas the seed of Citromelo rootstock tolerance Salinity, and the percentage of death Seedling only 22% in the fourth treatment هدفت الدراسة إلى تحديد تأثير محلول كلوريد الصوديوم في إنبات بذور بعض أصول الحمضيات، واستخدم في هذه الدراسة بذور الأصول: سيتروميلو، كاريزو سترانج، تروير سترانج، برتقال ثلاثي الأوراق، يوسفي كليوباترا والزفير وصممت التجربة بطريقة القطاعات العشوائية الكاملة وتضمنت أربع معاملات، وكل معاملة 5 مكررات وكل مكرر مكون من 20 بذرة. حللت النتائج باستخدام البرنامج الإحصائي SPSS واختبار ANOVA لتحديد الفروقات المعنوية بين المعاملات والأصول المدروسة. وبعد تحليل بيانات المشاهدة للمعاملات والأصول، أظهرت الدراسة عدم وجود أفعال متبادلة بين الأصول المدروسة والمعاملات الملحية، فزيادة التراكيز الملحية تبعاً للمعاملات تُنقص النسبة المئوية للإنبات على مستوى الأصل الواحد، لكن على مستوى الأصول كافة لا يوجد فروق معنوية لتأثير المعاملات في إنبات بذور الأصول، حيث تتشابه الأصول في معدل تناقص الإنبات فيها تبعاً للمعاملات الملحية، فهناك تقارب في النسب المئوية لإنبات البذور في المعاملة الأولى (الشاهد) والمعاملة الثانية (1000 ppm)، ثم نلاحظ انخفاض النسبة المئوية للإنبات في المعاملتين الثالثة والرابعة (3000,2000 ppm) باستثناء بذور الأصل سيتروميلو التي لم تتأثر النسبة المئوية لإنباتها بزيادة التراكيز المحلية، وكذلك الأصل تروير سترانج الذي لم يتأثر إنبات بذوره إلا بشكل بسيط في المعاملة الرابعة. أما من ناحية تأثير محلول كلوريد الصوديوم في استمرارية نمو البادرات فنلاحظ أن أعلى نسبة مئوية لموت البادرات كانت في الأصل يوسفي كليوباترا؛ إذ وصلت إلى 69.31% في المعاملة الرابعة (3000ppm)، في حين نجد أن بادرات الأصل سيتروميلو تحملت الملوحة، وبلغت النسبة المئوية لموت البادرات 22% فقط في المعاملة الرابعة.